Iodized Salt and Urinary Iodine Status among School-Aged Children: A Structured Narrative Review - Juan Maolidi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Iodine is essential for thyroid hormone synthesis, growth, and neurocognitive development in school-aged children. This review aimed to synthesize empirical evidence on the relationship between iodized salt exposure and urinary iodine concentration (UIC) among school-aged children and to identify factors affecting this relationship. A structured narrative review with a systematic literature search was conducted using Scopus and PubMed. The search identified 75 records, of which 23 studies were included after duplicate removal, title and abstract screening, and full-text assessment. Study quality was appraised using a JBI-based framework, and findings were synthesized narratively because of methodological heterogeneity. Overall, studies measuring household salt iodine content and UIC in the same population generally showed that adequate salt iodization was associated with better population iodine status. However, the relationship was modified by dietary iodine sources, salt storage and cooking practices, geographical context, and differences in exposure and UIC measurement. Evidence from population surveillance also supported the effectiveness of universal salt iodization while highlighting the risk of both insufficient and excessive iodine exposure. UIC should primarily be interpreted as a population-level indicator, as a single spot urine sample is insufficient for individual diagnosis. Comprehensive iodine monitoring should therefore combine salt iodine assessment, population UIC distribution, and relevant dietary and household factors.